The association between plasma IgG N-glycosylation and neonatal hypoxic–ischemic encephalopathy: a case-control study - Wang, Liangao; Lu, Xinxia; Wang, Meng; Zhao, Xuezhen; Li, Peirui; Zhang, Haitao; Meng, Qingtang; Zhang, Yujing; Wang, Yingjie; Wang, Wei; Ji, Long; Hou, Haifeng; et al. (Frontiers in Cellular Neuroscience, 2024)
Background: Hypoxic-ischemic encephalopathy (HIE) is one of severe neonatal brain injuries, resulting from inflammation and the immune response after perinatal hypoxia and ischemia. IgG N-glycosylation plays a crucial role in various inflammatory diseases through mediating the balance between anti-inflammatory and pro-inflammatory responses. This study aimed to explore the effect of IgG N-glycosylation on the development of HIE.This case-control study included 53 HIE patients and 57 control neonates.An ultrahigh-performance liquid chromatography (UPLC) method was used to determine the features of the plasma IgG N-glycans, by which 24 initial glycan peaks (GPs) were quantified. Multivariate logistic regression was used to examine the association between initial glycans and HIE, by which the significant parameters were used to develop a diagnostic model. Though receiver operating characteristic (ROC) curves, area under the curve (AUC) and 95% confidence interval (CI) were calculated to assess the performance of the diagnostic model.Results: There were significant differences in 11 initial glycans between the patient and control groups. The levels of fucosylated and galactosylated glycans were significantly higher in HIE patients than in control individuals, while sialylated glycans were lower in HIE patients (P<0.05). A prediction model was developed using three initial IgG N-glycans and fetal distress, low birth weight, and globulin.The ROC analysis showed that this model was able to discriminate between HIE patients and healthy individuals [AUC = 0.798, 95% CI: (0.716-0.880)].IgG N-glycosylation may play a role in the pathogenesis of HIE. PlasmaIgG N-glycans are potential noninvasive biomarkers for screening individuals at high risk of HIE.